"We Support You … to an Extent": Identities, Intersections, and Family Support Among First-Generation Students in a School of Social Work. Issue 2 (May 2022) - Mosier, Miranda
Family support is a critical part of college student retention. Given the strength of parental educational attainment in predicting access and persistence among college students (Choy, 2001), some have questioned the capacity for families to support first-generation college students. Family support may be especially critical for first-generation college students, who value interdependence more highly than continuing generation students (Stephens et al., 2012). This paper centers the perspectives of first-generation students in a school of social work and their experiences of family support. Focus group conversations were analyzed using the Listening Guide/Voice-centered relational data analysis (Brown & Gilligan, 1992). My interpretations were also guided by Black Feminist Thought (Crenshaw, 2000; Hill Collins, 1990) and Post-Modern Feminism (Campbell & Wasco, 2000), offering an intersectional, relationally-focused analysis of the nuances of family support. Findings highlight students' perceptions of family support, and the role that cultural expectations related to gender, race, and class play in shaping contradictory messages of family support. I offer implications for educators in schools of social work, including troubling narratives of social mobility, as part of the larger project of enhancing social justice in academia (Saulnier & Swigonski, 2006).